Hippo dictates signaling for cellular homeostasis and immune defense in Crassostrea hongkongensis hemocytes - Mao, Fan; Zheng, Xiaoying; Wong, Nai-Kei; Yi, Wenjie; Song, Jingchen; Fu, Shiwei; Xiang, Zhiming; Xiao, Shu; Bao, Yongbo; Yu, Ziniu; Zhang, Yang (Frontiers in Immunology, 2023)
The Hippo signalling pathway has emerged as a crucial regulator of cell fate and cellular homeostasis in immune processes. Yet, its roles in marine invertebrate immunity remain poorly understood. Here, we identified the full complement of Hippo pathway in the Crassostrea hongkongensis genome, which encompasses SAV1, MOB1, LATS, YAP/TAZ, TEAD, and MST. Quantitative PCR assays show that members of the Hippo pathway were dominantly expressed in hemocytes, and their expression levels rose sharply upon immune challenges. Crosstalk between the Hippo pathway and other immune pathways, particularly that of AP-1 and p53-dependent p21 signalling cascades, triggered off hemocytic apoptosis, which is functionally analogous to the canonical Mst-Lats-Yap signalling pathway in Drosophila and mammals. When MST (a core orchestrator of non-canonical Hippo signalling) was knocked down 45% relative to the control group by RNA interference, phagocytosis was retarded while efficiency of bacterial clearance was boosted in hemocytes, presumably due to mobilized antioxidant transcription by Nrf for maintaining immune homeostasis. These findings broadly diverged from mammalian observations. Overall, our present work provides fresh mechanistic insights into how the Hippo pathway orchestrates hemocytic functions in oysters, with implications for studies on its major forms and modifications in animal evolution.